Students’ Speaking Practices through Beelinguapp in an Islamic Senior High School - Sofiyah Sofiyah; Zainuddin Zainuddin; Nina Agus Hariati (Universitas Pahlawan Tuanku Tambusai, 2026)
Although speaking is a crucial skill for English as a Foreign Language (EFL) learners, students often have limited opportunities to practice it in classroom settings. While previous studies have highlighted the potential of Mobile-Assisted Language Learning (MALL), few have examined how specific applications such as Beelinguapp support speaking practices in real classroom contexts, particularly in low exposure environments. This study aims to explore students’ speaking practices using the Beelinguapp application in an Islamic Senior High School. A qualitative case study was conducted involving 20 eleventh-grade students, with three students and one English teacher selected through purposive sampling for in-depth interviews. Data were collected through one classroom observation and semi-structured interviews. The findings show that students practiced speaking through listening, repetition, and story retelling. The application supported pronunciation, vocabulary development, and engagement, although challenges such as limited vocabulary and exposure remained.